Crescimento de Araucaria angustifolia (Bertol) Kuntze sob manejo florestal na região noroeste do Rio Grande do Sul - Lambrecht, Fernanda Raquel (2017)
The objective of this study was to determine the growth rate of Araucaria angustifólia in a forest fragment in the northwest RS region and to evaluate its growth 20 years after the implementation of a Sustainable Forest Management Plan (PMFS). The study was carried out in the municipality of Erval Seco, RS in a fragment with about 50 ha. Were demarcated 31 sample units (1,000 m² each) in the forest fragment, totaling an area of 3,1 ha. Were sampled 62 Araucaria trees, with DBH≥10 cm. The araucaria growth pattern was tested to fit an equation that satisfactorily represented individuals' growth and the best representation of the data was obtained by Johnson-Shumacher. The correlation of the climatic variables with the araucaria increment data was performed and the variables that influenced the most were minimum temperature and cloudiness, demonstrating that these elements can be considered limiting in araucaria growth. The mean DAP found was 47 cm (11,7 – 73,8 cm). The competition analysis of araucaria individuals was performed through the distance-dependent competition indices (IDD) and indices independent of the distance (IID). Among the 13 indexes tested, the ones that presented better performance were Stage (1973) (IID9) and Moore et al. (1973) (IDD13). Which express by the authors that the lower the value of the index the greater the competition (for both cases). Therefore, the larger the competitors' diameter, the lower the value of the index (and the greater the competition, the ratio is the inverse). In relation to the araucaria growth rate, the youngest individuals (1st class-10-24,9) had the lowest increase, the 3rd class (25-49,9) and the 2nd class (50- 75) present the individuals with the greatest increase in the last 20 years. Araucaria trees responded positively to the forest management carried out in 1993, showing a larger increase (1993-2013) in the year of 2000 and since 2010 showed a decrease in the increment, demonstrating that a new intervention could be carried out from that moment. It was possible to notice that in many cases the laws prohibit the cut of araucaria, seeking to protect it from extinction, but to prohibit the cut is not the proper way to guarantee the conservation and preservation of the species. Public policies are needed that encourage the maintenance of the species (conservation) and its economic value.